-19-(-4)=x

Simple and best practice solution for -19-(-4)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19-(-4)=x equation:


Simplifying
-19 + -1(-4) = x

Multiply -1 * -4
-19 + 4 = x

Combine like terms: -19 + 4 = -15
-15 = x

Solving
-15 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-15 + -1x = x + -1x

Combine like terms: x + -1x = 0
-15 + -1x = 0

Add '15' to each side of the equation.
-15 + 15 + -1x = 0 + 15

Combine like terms: -15 + 15 = 0
0 + -1x = 0 + 15
-1x = 0 + 15

Combine like terms: 0 + 15 = 15
-1x = 15

Divide each side by '-1'.
x = -15

Simplifying
x = -15

See similar equations:

| -10-(-5)=x | | -18=6x-4x | | 3/4=z/16 | | 2a+-5b+5a+-1b= | | c^2=40-3c | | 8x-9+7x= | | 55=5/9(f-32) | | 7-3x=5x | | 2a-7=1 | | 3(x+3)=4(x-1) | | (-3y+18)=y | | 4a-6(a+1)=2(a+5) | | 4(2n-7)=12 | | 4/7+15= | | 3(2n-8)=4(-1-n) | | 9=-(3-x) | | 2y+3-5y+9= | | y=-0-2 | | 11x-2=130 | | -7+x=4 | | 4y-4-6y-4= | | (2x+7)+(7x-7)=63 | | X-13=-9 | | -3(5z-3)-3(3z+7)-17z= | | 3h+5h-5=11 | | (6x-4)-(4x+2)= | | 25v^2-1= | | 6c-4c+2=-(-c+11) | | 5d-9=-29 | | (6x-8)-(3x+5)= | | 16x-6= | | x+5x+90=180 |

Equations solver categories